Autoimmune Encephalitis in Latin America: A Critical Review - Vasconcelos, Gabriel de Albuquerque; Barreira, Rodrigo Montenegro; Antoniollo, Karmelita Emanuelle Nogueira Torres; Pinheiro, Alina Maria Nuñez; Maia, Cíntia Fernandes Rodrigues; Alves, Danyela Martins Bezerra Soares; Nóbrega, Paulo Ribeiro; Braga-Neto, Pedro (Frontiers in Neurology, 2021)
Autoimmune encephalitis is an increasingly recognized cause of encephalitis. The majority of case series report patients in developed countries in the northern hemisphere. Epidemiologic features of autoimmune encephalitis in Latin America are still unclear. The aim of the study was to perform a review of the clinical presentation of autoimmune encephalitis in Latin America and compare to world literature. References were identified by a literature search and selected on the basis of relevance to the topic and authors’ judgment. We selected clinical studies and case reports published from 2007 to 2019 including patients from Latin American countries. Of the 379 patients included, the majority were anti-NMDA receptor encephalitis (93.14%), followed by anti-VGKC-complex encephalitis (N = 17; 4.48%), anti-GAD encephalitis (N = 9; 2.37%), anti-AMPA receptor encephalitis (N = 1; 0.26%), anti-GABA receptor encephalitis (N = 1; 0. 26%), anti-mGluR5 encephalitis (N = 1; 0. 26%), and anti-mGluR1 encephalitis (N = 1; 0. 26%). Reported cases of Anti-NMDA encephalitis in Latin-America had a slight female predominance, lower prevalence of associated tumors and lower incidence of extreme delta brush. Autoimmune encephalitis is possibly underdiagnosed in underdeveloped countries. Its outcome after treatment, however, appears to be similarly favorable in Latin American patients as has been reported in developed countries based on available case reports and case series. Regional specificities in the manifestation of autoimmune encephalitis could be related to epidemiologic factors, such as the presence of different triggers and different genetic and immunologic background, that need to be studied by future research.